Respon Pertumbuhan dan Hasil Tanaman Kacang Tanah terhadap Pemberian Dosis Pupuk Hayati Di Lahan Podsolik - M. Fauzi Noor; Mahdiannoor; Nur Hafizah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2018)
Peanut plants are the second most important leguminous plants after soybeans in Indonesia. The growth and yield of peanut plants on podsolic land are not good, the problem of podsolic soil is acidic soil reaction, high Al content, low nutrient content, so it needs liming and fertilization and good management so that the soil becomes productive and not damaged. Biofertilizer is an alternative use of fertilizer. This research was carried out on podsolic land in Banua Tinggal Village, Labuan Amas Selatan District, Hulu Sungai Tengah Regency, which began from April to July 2017. The study aimed to (i) determine the response of growth and yield of peanuts to the provision of biological fertilizers on podsolic land and ) get the best dosage of biofertilizer for growth and yield of peanuts on podsolic fields. This study used a Randomized Block Design (RBD) with four treatments and six groups so that there were 24 experimental units. Provision of biological fertilizer is (h0) 0 t.ha-1 = 0 kg. plot-1, (h1) 50 t.ha-1 = 7.5 kg.plot-1, (h2) 70 t.ha-1 = 10.5 kg.plot-1, (h3) 90 t.ha-1 = 13.5 kg.plot-1. The variables observed were plant height, number of leaves, age stem diameter at flowering, number of plant pods, wet weight of plant pods, and weight of 100 dry seeds. The results showed that the administration of biofertilizer affected the growth and yield of peanut plants and treatment (h3) 90 t.ha-1 = 13.5 kg.plot-1 was the best treatment for the growth and yield of peanut plants.